PERLINDUNGAN HAK EKONOMI PENCIPTA E-BOOK PADA SITUS BUKU GRATIS MERESPON PERKEMBANGAN HUKUM INFORMATIKA DAN TRANSAKSI ELEKTRONIK - Arif Rahman; Efridani Lubis; Agus Surachman (JURNAL ILMIAH LIVING LAW, 2020)
The purpose of this research is: 1) To find out and analyze the protection of the economic rights of the creators of e-books on free book sites in response to the development of informatics law and electronic transactions. 2) To find out and analyze dispute resolution violations of the economic rights of e-book creators on free book sites in response to developments in informatics law and electronic transactions. The research method used in this study is normative juridical research that takes a qualitative approach that looks at and analyzes the legal norms in existing laws and regulations and sociological research is complementary data as primary data. The results of this study are: 1) Protection of the economic rights of e-book creators on free book sites in response to the development of informatics law and electronic transactions, related to the protection of creators' economic rights in accordance with the Copyright Law that an e-book is a copyrighted work produced by the creator, so in this case the creator has a part of the exclusive rights in the form of economic rights from the results of the e-book, the economic rights are protected by Article 8 and Article 9 of the Copyright Law on Economic Rights. While the ITE Law provides the protection of the creator's economic rights in terms of electronic transactions, because of the nature of the distribution of e-books using electronic media, where the legal electronic media is included in the realm of the ITE Law. 2) Settlement of disputes on economic violations of e-book creators on free book sites in response to developments in informatics law and electronic transactions, namely through voluntary mediation carried out by parties outside the court in settling disputes over copyright infringement e-books in the realm of civil law.